Created in the Image and Likeness of God: An Exposition of Relationship in Human Creation - Yohanes Verdianto (Budapest International Research and Critics University, 2022)
After God created plants, animals, and light objects, God created humans. The first man (Adam) was formed from the dust of the ground and breathed into his nostrils the breath of life to become a living man. After that, God formed a woman (Eve) from the rib of a human (Adam), both of them lived happily in their relationship with God in the garden of Eden, until finally they were tempted by the serpent and expelled from the garden of Eden. This study aims to find out what relationships exist in the Garden of Eden, from the creation of man to his fall. This paper argues that four types of relationships exist. First is the relationship between the Creator and humans, fellowship and worship by humans to God the Creator. Second, the relationship between humans and other created beings, where God's original purpose is for humans to control and manage other created beings. Third, the relationship between humans (Adam) and humans (Eve) symbolizes God's love for humans so that humans must love each other both horizontally and vertically. Fourth, the relationship between humans and snakes, where they were tempted by the serpent and were eventually expelled from the Garden of Eden, but there was a promise of redemption that God gave them. This paper uses a qualitative method with a descriptive analysis approach. The literature used is the main source regarding the fellowship between God the Creator and His human creation and the various relationships that existed in the Garden of Eden. Secondary sources are needed to compare and provide input in connection with this research.